The encyclopedia of mass spectrometry : Vol. 9 : historical perspectives : Pt. A : the development of mass spectrometry - Nier, Keith A.; Yergey, Alfred L.; Gale, P. Jane (Paula Jane), 1946- (Amsterdam : Elsevier, 2015)
Volume 9: Historical Perspectives, Part A: The Development of Mass Spectrometry of The Encyclopedia of Mass Spectrometry describes and analyzes the development of many aspects of Mass Spectrometry. Beginning with the earliest types of Mass Analyzers, Historical Perspectives explores the development of many different forms of analytical processes and methods. The work follows various instruments and interfaces, to the current state of detectors and computerization. It traces the use of Mass Spectrometry across many different disciplines, including Organic Chemistry, Biochemistry, and Proteomics; Environmental Mass Spectrometry; Forensic Science; Imaging; Medical Monitoring and Diagnosis; Earth and Planetary Sciences; and Nuclear Science. Finally, the book covers the history of manufacturers and societies as well as the professionals who form the Mass Spectrometry community. Also available: Volume 9: Historical Perspectives, Part B: Notable People in Mass Spectrometry briefly reviews the lives and works of many of the major people who carried out this development. Preserves the history and development of Mass Spectrometry for use across scientific fields Written and edited by Mass Spectrometry experts Coordinates with Volume 9: Historical Perspectives, Part B: Notable People in Mass Spectrometry, a collection of short biographies on many of the major people who carried out this development.
1.7Computers and MS Library Search Algorithms -- 1.8Computers and Mass Spectrometers in the 1980s and Beyond -- 2Acknowledgements -- References -- The Development of Computer Data Systems in Quadrupole Mass Spectrometers -- References -- A History of the Development of Mass Spectral Databases -- 1Introduction -- 1.1Early Collections of Spectra -- 2Advent of Computers: Databases and Early Search and Retrieval Programs -- 3Consolidation -- 3.1Origin of the NIH and NIST-EPA-NIH Collections -- 3.2Origin of the Wiley Collection -- 4Evaluations and Rivalries -- 5Specialty Databases -- 6Legacy -- 7Conclusions -- References -- A History of Mass Spectrometry in Nuclear Science -- 1 Introduction -- 2 The Binding Energy Curve -- 3 Mass Spectrographs -- 4 Atomic Masses -- 5 Nuclear Fission -- 6 Conclusions -- Acknowledgments -- References -- Mass Spectrometry and the Separation and Enrichment of Isotopes -- 1 Introduction -- 2 Discovery of Isotopes -- 3 Production of Isotopes for Research and Commerce -- 4 Conclusion -- Acknowledgments -- References -- The Development of Mass Spectrometry in the Earth and Planetary Sciences -- 1 From the Beginning to World War II -- 2 From World War II to 1960 -- 3 From 1960 to 1980 -- 4 Since 1980 -- References -- Mass Spectrometric Methods for the Determination of Thermodynamic Data -- 1Introduction -- 2Ionization Energies -- 3Appearance and Dissociation Energies -- 3.1Photodissociation -- 3.2Collision-induced Dissociation -- 3.3Dissociation Induced by Electrons -- 4Ion Affinities and Solvation Energies -- 5Electron Affinities -- 6Neutrals -- 7The Electron -- 8Conclusion -- References -- The Beginnings of Organic Mass Spectrometry -- 1 Introduction -- 2 Mass Spectrometry in the US Petroleum Industry -- 2.1 Analysis of Petroleum Fractions -- 2.2 The CEC 21-101 Mass Spectrometer.
Includes bibliographical references.
Print version record.
Keywords: Mass spectrometry -- Encyclopedias; Scientists -- Encyclopedias; Mass spectrometry; Scientists; Electronic books; Encyclopedias